2010
DOI: 10.1186/1471-2091-11-37
|View full text |Cite
|
Sign up to set email alerts
|

The effects of oligomerization on Saccharomyces cerevisiae Mcm4/6/7 function

Abstract: BackgroundMinichromosome maintenance proteins (Mcm) 2, 3, 4, 5, 6 and 7 are related by sequence and form a variety of complexes that unwind DNA, including Mcm4/6/7. A Mcm4/6/7 trimer forms one half of the Mcm2-7 hexameric ring and can be thought of as the catalytic core of Mcm2-7, the replicative helicase in eukaryotic cells. Oligomeric analysis of Mcm4/6/7 suggests that it forms a hexamer containing two Mcm4/6/7 trimers, however, under certain conditions trimeric Mcm4/6/7 has also been observed. The functiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 63 publications
(89 reference statements)
1
4
0
Order By: Relevance
“…Our data support the arrangement model of the Mcm4/6/7 hexamer for the six subunits of spMCM (Figure 7B) that was proposed for S. cerevisiae MCM [26], and human MCM [23,24,42]. An alternative arrangement model, in which binding between Mcm6 and Mcm7 occurs, was proposed in a previous report [43]. The literatures have some disagreement about the interactions between Mcm6 and Mcm7.…”
Section: Discussionsupporting
confidence: 89%
“…Our data support the arrangement model of the Mcm4/6/7 hexamer for the six subunits of spMCM (Figure 7B) that was proposed for S. cerevisiae MCM [26], and human MCM [23,24,42]. An alternative arrangement model, in which binding between Mcm6 and Mcm7 occurs, was proposed in a previous report [43]. The literatures have some disagreement about the interactions between Mcm6 and Mcm7.…”
Section: Discussionsupporting
confidence: 89%
“…3C). In order to evaluate the size of Claspin more precisely, Claspin was treated with glutaraldehyde (Ma et al 2010) and analyzed on a native gel and SDS-PAGE (Fig. 3C).…”
Section: Size Of Human Claspin Proteinmentioning
confidence: 99%
“…67 MCM4/6/7 proteins exhibit distinct functions when the ATP binding sites undergo mutations. 68 It should also be mentioned that MCM7 is required for ATP hydrolysis and DNA helicase via its ATP binding motif. 69 Nuclear magnetic resonance (NMR) structure studies revealed that the C-terminus of MCMs comprises a winged helix (WH) domain.…”
Section: Cmg Complexmentioning
confidence: 99%
“… 67 MCM4/6/7 proteins exhibit distinct functions when the ATP binding sites undergo mutations. 68 It should also be mentioned that MCM7 is required for ATP hydrolysis and DNA helicase via its ATP binding motif. 69 …”
Section: Evolution Of the Core Replication Proteinsmentioning
confidence: 99%
See 1 more Smart Citation